2015
DOI: 10.3345/kjp.2015.58.8.294
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of pelvic ultrasonography for the diagnosis of central precocious puberty in girls

Abstract: PurposeIt is difficult to differentiate between central precocious puberty (CPP) and premature thelarche (PT) in girls. The aim of this study was to investigate the diagnostic usefulness of pelvic ultrasonography to distinguish between CPP and PT in girls with early breast development.MethodsThis study included girls with early breast development who visited the clinic between January 2012 and December 2013. Clinical, laboratory, and pelvic ultrasonographic data were evaluated. CPP and PT were confirmed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
2
17
0
1
Order By: Relevance
“…Several studies have reported on the usefulness of ultrasound for CPP diagnosis [14-16]. Yu et al [14] reported that uterine length, transverse diameter, fundus, volume, and cross-sectional area were significantly larger on ultrasound in CPP patients (uterine length: 2.45±0.50 cm vs. 2.63±0.49 cm, P =0.015; uterine volume: 0.95±0.62 cm 3 vs. 1.35±0.76 cm 3 , P <0.001). However, these parameters are not useful for diagnostic purposes because they overlap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the usefulness of ultrasound for CPP diagnosis [14-16]. Yu et al [14] reported that uterine length, transverse diameter, fundus, volume, and cross-sectional area were significantly larger on ultrasound in CPP patients (uterine length: 2.45±0.50 cm vs. 2.63±0.49 cm, P =0.015; uterine volume: 0.95±0.62 cm 3 vs. 1.35±0.76 cm 3 , P <0.001). However, these parameters are not useful for diagnostic purposes because they overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine length was measured from the fundus to the external opening at the maximum length of the midsagittal section in an anteroposterior direction. Ovary volume was estimated using the ellipse formula (length×height×transverse diameter×0.5233) [14], and the side of the ovary was noted.…”
Section: Methodsmentioning
confidence: 99%
“…for example, some have reported a significantly higher FCR in PP (22,24,27), whereas others have not (12,28). After pooling these studies, we found a meaningful difference in FCR between the PP and PT groups, suggesting that this parameter could successfully differentiate PP from PT.…”
Section: Summary Of Main Findingsmentioning
confidence: 58%
“…Previously, it has been, however, primarily indicated to exclude organic causes of peripheral early puberty, such as ovarian cysts and tumors (11)(12)(13). Moreover, international consensus on the definite cutoffs for ultrasonography measurements in PP is unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…Một số nghiên cứu đưa ra các tiêu chuẩn chẩn đoán cho nồng độ FSH nền trong huyết thanh nhưng có độ nhạy và độ đặc hiệu thấp [3], [11]. Ngược lại, nồng độ hormone sinh dục nữ (Estradiol) huyết thanh lại không có sự khác biệt giữa 2 nhóm nghiên cứu (bảng 3.7), tương tự với các nghiên cứu trước đây, của Liat de Vries (2004), Jung Yu (2015) [8], [10]. Tương đồng với một số nghiên cứu trước đây, bảng 3.9 cho thấy các chỉ số siêu âm tử cung buồng trứng có giá trị trong chẩn đoán phân biệt dậy thì sớm trung ương và tuyến vú phát triển sớm bao gồm chiều cao tử cung, chiều rộng tử cung, chiều trước sau tử cung, thể tích tử cung và thể tích buồng trứng với p < 0,05 [9],[10],[12],[13].…”
Section: đặC đIểm Lâm Sàng Và Cận Lâm Sàng Của Dậy Thì Sớm ở Trẻ Gáiunclassified